Colonial War and Propaganda War: A New Approach to Camilo Polavieja’s Philippine War (1896-1897) - Díaz Esteve, Laura; Garcia-Balañà, Albert (Hispania Nova, 2025)
This article analyses the “double campaign” that Captain General Camilo Polavieja conducted during the Philippine Revolution of 1896-1897. On the one hand, it discusses the military campaign that Polavieja conducted in Cavite. Knowing that he would meet stiff resistance, including combatants and civilians, he waged an all-out war that ignored the principles of waging war “with humanity” that were being codified. Knowing the bad press that this could arouse and how damaging it could be to his political aspirations, Polavieja also led a propaganda war in the Hong Kong press, which was international in scope and very harsh on Spain’s handling of the uprising. The general justified his methods on the grounds that they were the only effective means of dealing with what he portrayed as an illegitimate and ferocious insurgency that did not respect the Laws of War and should, therefore, be excluded from their protection.
Keywords: Philippine Revolution, 1896-1897; Camilo Polavieja; colonial warfare; public opinion; Hong Kong